Building systems in interior design - Hurt, Samuel L. (Routledge, 2018)
"Building Systems in Interior Design takes an entirely new approach to teaching this essential topic for Architects, Designers and Building Engineers. Written to prepare students for the real world and packed with practical examples, the book will foster an understanding of specific issues that are critical to those features of technical systems that most directly affect design. The book stresses the ever-present nature of these systems: they are everywhere, all the time"--Provided by publisher.